The impact of in hospital patient-education intervention on older people's attitudes and intention to have their benzodiazepines deprescribed: a feasibility study - Danijela Gnjidic; Hui Min Magdalene Ong; Celeste Leung; Jesse Jansen; Emily Reeve (SAGE Publishing, 2019)
Background: Long-term benzodiazepine use in the older population is common and is associated with significant harm. The provision of a patient-educational booklet during hospitalization may encourage patients to discuss review and possible deprescribing of benzodiazepine therapy with their health professionals. The aim of this study was to assess the feasibility and effect of a patient empowerment intervention in hospital inpatients on patient initiation of a discussion about deprescribing benzodiazepines versus usual care. Methods: A feasibility interventional study using a patient-empowerment education intervention was conducted at a Sydney teaching hospital. Patients aged ⩾ 65 years, prescribed a benzodiazepine, and able to provide consent were invited to participate in the study. Participants were randomly allocated to intervention or control group (1:1). Intervention participants received the patient-empowerment booklet and control received usual care. All participants received 1-month follow-up phone interviews to assess medication and attitudinal changes. Results: A total of 42 participants were recruited (20 intervention and 22 control). The average age was 71.5 (interquartile range: 69.0-80.3) and 54.8% were females. There was no difference in baseline characteristics between intervention and control groups ( p > 0.05). At baseline, 65.0% of participants (53.0% intervention, 86.0% control) were not concerned about the potential benzodiazepine side effects. Twenty-nine participants (15 intervention and 14 control) completed 1-month follow up; 22 participants (11 intervention and 11 control) were discharged on the benzodiazepine. Among these, 13 (59.1%) had ceased benzodiazepine at 1-month follow up [46.2% ( n = 6) intervention; 53.8% ( n = 7) control]. In the intervention group, 33.3% ( n = 5) of participants had initiated a discussion with their doctor or pharmacist about stopping the benzodiazepine compared with 35.7% ( n = 5) in the control group. Conclusion: Cessation of benzodiazepines 1 month following discharge was common. Future larger studies are required to confirm the effectiveness of providing a patient-empowerment booklet on reducing benzodiazepine use and other potentially inappropriate medications.